2011
DOI: 10.1007/s10865-011-9389-6
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective and weight management behaviors in newly diagnosed Type 2 diabetes: a mediational analysis

Abstract: The primary objective of the current study was to examine the extent to which domain-specific time perspective predicts weight management behaviors (dietary behavior and physical activity) among those newly diagnosed with Type 2 diabetes. A secondary objective was to test potential mediators of the hypothesized effect (behavioral intention, self-efficacy and control beliefs). A total of 204 adults newly diagnosed (≤6 months) with Type 2 diabetes participated in the study, which included a baseline assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 34 publications
9
49
0
5
Order By: Relevance
“…The present findings indicate that for individuals scoring high in Agreeableness and low in Neuroticism, this prospective process with respect to health may rely upon more than current health states and involve viewing future health through an optimistic lens. The benefits of taking a positive view of the future for motivating important health behaviors are well documented, especially for those dealing with an ongoing health issue [37]. Accordingly, high Agreeableness and low Neuroticism may indicate who may be more likely to continue health-promoting behaviors key for disease management because they view their future health positively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present findings indicate that for individuals scoring high in Agreeableness and low in Neuroticism, this prospective process with respect to health may rely upon more than current health states and involve viewing future health through an optimistic lens. The benefits of taking a positive view of the future for motivating important health behaviors are well documented, especially for those dealing with an ongoing health issue [37]. Accordingly, high Agreeableness and low Neuroticism may indicate who may be more likely to continue health-promoting behaviors key for disease management because they view their future health positively.…”
Section: Discussionmentioning
confidence: 99%
“…Because theory and research indicate that positive expectations for the future can motivate current health-relevant behaviours [36][37][38], future self-related health (FSRH) may be a particularly important concept to study in individuals living with a chronic illness to better understand their current health-promoting and disease management behaviors. From this perspective, the translational value of the current findings could be optimized by identifying individuals with IBD or arthritis who are low in Agreeableness and high in Neuroticism and may be more likely to view their future health more negatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One theoretical framework, temporal self-regulation theory (Hall & Fong, 2013), posits that time perspective should exert its effect on behaviors via intention strength; that is, future oriented individuals engage in healthier behaviors because of their stronger motivation (i.e., intentions) to do so; such stronger intentions, in turn, are thought to be generated by their greater sensitivity to the long-term (or nonimmediate) contingencies for their own behavior. There are only two prior studies that have examined intention as a mediator of the effect of time perspective on health behaviors, both of which have found support for the link (Hall, Fong, & Cheng, 2012; Hall et al, 2012). In our earlier analysis of a much more limited subset of this data (3 years; Hall et al, 2012), we found that future orientation predicted quit attempts, but the data was not yet complete for the full follow-up interval (now nearly 10 years cumulatively).…”
Section: Prior Research On Time Perspective Health Behaviors and Medmentioning
confidence: 99%
“…Results suggest that fi rst-timers can concentrate on getting started with AcP before considering CP, which should be more useful in maintenance (Scholz et al, 2008). In addition to the formulation stage-appropriate specifi c plans, they also highlight the importance of sustaining volition over time, hence self-regulatory effort, as proposed by Hall, Fong &Cheng (2011), andHagger et al (2010).…”
Section: Discussionmentioning
confidence: 86%